Uremia aggravates left ventricular remodeling after myocardial infarction - Dikow, Ralf; Schmidt, Ulrike Stefanie; Kihm, Lars Philipp; Schaier, Matthias; Schwenger, Vedat; Groß-Weissmann, Marie-Luise; Katus, Hugo; Zeier, Martin; Hardt, Stefan (American journal of nephrology, 2010)
Background: Renal failure is a well-established cardiovascular risk factor. We hypothesized that uremia negatively affects post-myocardial infarction (MI) remodeling and left ventricular (LV) function and examined the pathohistological correlations. Methods: Subtotally nephrectomized rats (SNX) and controls with MI only (MIC) were examined 1, 4 and 8 weeks after MI. MI size, ejection fraction (EF), cardiac fibrosis, vascular density and cardiomyocyte density were studied. Results: The extension of MI was 0.08 ± 0.02 in SNX versus 0.06 ± 0.02 in MIC rats (p < 0.031). Prior to MI, EF was comparable in SNX and MIC (74 ± 3 vs. 72 ± 2%, n.s.). Despite a relatively small infarct size EF in SNX decreased to 58 ± 4% 1 week after infarction and progressively worsened to 51 ± 4% after 8 weeks. In MIC animals EF only slightly decreased 1 week after MI (70 ± 3%) and remained unchanged at follow-up. In SNX animals LV end-diastolic diameter continuously increased following MI throughout the study period indicating accelerated remodeling. Furthermore, accelerated myocardial fibrosis was already notable 1 week after MI in SNX animals and the volume density of capillaries and cardiomyocytes was significantly lower in SNX rats. Conclusion: MI in experimental uremia is associated with progressive impairment of LV function, LV dilatation and accelerated myocardial fibrosis.
Gesehen am 02.02.2023